Modern electrosynthetic methods in organic chemistry - Atobe, Mahito, 1969-; Marken, Frank (Boca Raton : CRC Press, 2018)
Modern Electrosynthetic Methods in Organic Chemistry introduces readers to new ways of making materials and compounds using low waste processes, employing energy from electricity rather than chemical reagents. It explores electro-organic synthesis, which offers clean synthesis tools as well as unusual reaction intermediates and reaction types. Despite applications previously remaining niche, due to the advent of microfluidic reactors this book is a must-read for industry professionals and academics alike. It targets specific areas of recent progress and development in the field that show high novelty and potential, at the same time inviting a wider range of applications in green and clean technology.
5.2 Cathodic Conversions at Boron-Doped Diamond Electrodes5.2.1 Carbon Dioxide Reduction; 5.2.2 Cathodic Reductive Coupling of Methyl Cinnamates; 5.2.3 Reduction of Oximes; 5.3 Anodic Transformations at Boron-Doped Diamond Electrodes; 5.3.1 Alkoxylation Reactions; 5.3.2 Fluorination; 5.3.3 Cyanation; 5.3.4 Cleavage of C, C-Bonds; 5.3.5 Electrochemical Amination Reactions; 5.3.6 Anodic Phenol Coupling Reaction; 5.4 Novel Concepts and Electrode Materials for Electrochemical Reductions; 5.4.1 Improvement of Existing Cathodes; 5.4.2 Novel Cathode Materials; 5.5 Summary; References.
OCLC-licensed vendor bibliographic record.
Keywords: Organic compounds -- Synthesis; Electrochemistry; Chemistry, Physical and theoretical; SCIENCE -- Chemistry -- Organic